PERLAKUAN AKUNTANSI PEMBIAYAAN MULTIJASA UMROH (STUDI KASUS PADA BANK JATIM SYARIAH CAB. DARMO SURABAYA) - NIRWESTHI, FISHATANIA (Jurnal Akuntansi AKUNESA, 2015)
Abstract Sharia bank as a financial institution which is functioning as the mediator between the excessive funds holder and the one who needed funds for business and other activities which correspond with the Islamic sharia principles, should not be apart from transparency or accounting records. All transaction processes from the products of sharia bank have to be recorded correctly according to the financial accounting standard that is generally accepted such as PSAK, which includes the process of financing the Umrah multi services. This research aimed to comprehend and analyze the accounting treatments of financing the Umrah multi services in Bank Jatim Sharia's Darmo Surabaya branch office. The type of research is a qualitative research based on a case study. Furthermore, the approach used in this research to collect and process the data in the form of documents are content analysis document approach. The result of this research showed that the accounting treatments applied by Bank Jatim Sharia's Darmo Surabaya branch office has corresponded with the PSAK 107 towards the ijarah from the acknowledgement and measurement, as well as the presentation and disclosure. Keywords: Financing, Ijarah, PSAK 107